Futuros do jornalismo na era da "informação genérica" - Gradim, Anabela (2019)
After more than a century of stabilizing a popular mass journalism model centered on audiences and the notion of public service, as a counterpoint to the 17th and 19th century party press, the sector is experiencing a moment of disruption unparalleled in its history. In order to make a critical reading of this historical leap, we will argue that there are visible signs of dissolution of the field in the unprofessionalization of its agents, and that this transformation of the industry stems from changes in the mode of production and business models brought about by the digitization and ubiquity of content. Since the media is not the only sector touched by this revolution in labor relations, it is a crucial area for the realization of Western-type liberal democracies. From a survey conducted with media professionals from the central region of Portugal, we observed how these trends are developing, proposing the refocusing of the profession and business models on service to the public. We then seek to cross-check these data with those we collect from journalism students, future professionals in the area, in an attempt to understand how the field of journalism may evolve.